Assessment the Aquifer Characteristics in Meuang Saen Village, Sepon District, Savannakhet Province - KEOKHAMPHUI, Khaykeo (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
Assessment the Aquifer Characteristics in Meuang Saen Village, Sepon District, Savannakhet Province aims to study the hydrological properties of the groundwater and to know the specific capacity of the groundwater (Specific Capacity, Sc) and evaluate the appropriate water supply (Maximum yield) to be used in the future to determine the rate of water pumping (Optimum yield/Maximum Available yield). The Methodology of this study is selected 2 borewells to conduct pumping test by 2 methods as constant test method and step test method. The result of pumping test calculates by finding maximum yield of an aquifer for slecting suitable pumping system. The result of the study found that transmissivity, Maximum yield and specific capacity of borewell 1 equal to 8.48E-05 m2/s, 3.10 m3/hr and 0.16 m3/s and borewell 2 equal to 2.36E-04 m3/hr/m, 3.60 m3/hr, 0.14 m3/hr/m., respectively. Accordint to the result of pumping test of 2 borewells can be concluded that the rock layer in research area is a type of sandstone, which is a rock layer that has the ability to release a low amount of water from a aquifer or the ability to allow a small amount of water to flow through the formation is evident from the water distribution coefficient analysis at mentioned above.